Optimization of Extraction from Sappan Wood and Its In uence on Food Bacterial Contaminants - Putranti Adirestuti; Ririn Puspadewi; Athina Mardatillah; Dismayana Anggita; Meidy Helena; Alfa Octavia; Yosinta Putri (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Sappan wood has already known as an ingredient of jamu, especially in Central Java. If it dissolved in hot water, it will show a red color and has been used as health drink for blood current obstruction, diarrhea, blood cough, dysentry, malaria and tetanus. The red pigment of sappan wood contained avonoid and polyphenol. The two kind of extractions of sappan wood used in this experiment were obtained by boiling water extraction at 90oC in 15 minutes and maceration in ethanol 50% overnight. The aim of this research was to nd the potential of inhibiting sappan wood for presence of bacterial contaminants in food, such as Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa in several time storages. Microbial examination by observing visual characteristics of damage to the food model and the decrease number of food bacterial contaminants. The result showed that ethanol extract 10% of sappan wood inhibited a food bacterial contaminants in three days at cold temperatures storage (8-10OC), and percent decrease population of E. coli, S. aureus and P. aeruginosa were 99.74%, 96.28%, and 99.88%, respectively. Key words : Ethanol extract, food contaminant bacterias, inhibiting, sappan wood, water extract